TNF-α and Microglial Hormetic Involvement in Neurological Health & Migraine - Richard P. Kraig; Heidi M. Mitchell; Barbara Christie-Pope; Phillip E. Kunkler; David M. White; Ya-Ping Tang; George Langan (SAGE Publishing, 2010)
Environmental enrichment, i.e., increased intellectual, social, and physical activity makes brain more resilient to subsequent neurological disease. The mechanisms for this effect remain incompletely defined, but evidence shows tumor necrosis factor-alpha (TNF-α) is involved. TNF-α, at acutely high levels, possesses the intrinsic capacity to enhance injury associated with neurological disease. Conversely, the effect of TNF-α at low-levels is nutritive over time, consistent with physiological conditioning hormesis. Evidence shows that neural activity triggers low-level pro-inflammatory signaling involving TNF-α. This low-level TNF-α signaling alters gene expression, resulting in an enhanced resilience to disease. Brain-immune signaling may become maladaptive when increased activity is chronic without sufficient periods of reduced activity necessary for nutritive adaptation. Such tonically increased activity may explain, for example, the transformation of episodic to chronic migraine with related increased susceptibility to spreading depression, the most likely underlying cause of this malady. Thus, TNF-α, whose function is to alter gene expression, and its principal cellular source, microglia, seem powerfully positioned to orchestrate hormetic immune signaling that establishes the phenotype of neurological health and disease from brain activity.